André Malraux at the Heart of Romain Gary’s Imaginary Museum - Barkate, Jonathan (Literatūra, 2022)
Malraux is in the center of Gary’s imaginary museum. His name and thought are regularly quoted in Gary’s work. When the author of Pour Sganarelle, La Promesse de l’aube and La Danse de Gengis Cohn refers to the metamorphosis and the museum without walls – two concepts Malraux invented –, he uses Malraux’s image and writings to reveal how himself sees the world and the artist’s role. To analyse those quotes leads to reading Gary’s work through the lens of Malraux’s. It also shows how Gary portrays himself as a « conqueror of the impossible » while making his model embody his own aesthetic and ethical aspirations. His selfportrait as a jumping jack makes Gary follow the path of his friend, who elevated Man by softening his condition.